TINJAUAN PEMANFAATAN PERPUSTAKAAN OLEH GURU DAN SISWA DI SMK NEGERI I PADANG - 722-727 , Iwan Gunawan (Universitas Negeri Padang, 2015)
ABSTRACT Iwan Gunawan, 2015: Overview and Use of Library By Teacher and Students at SMK Padang. This study originated from the fact that the use of the library SMK 1 Padang yet optimally act as a vehicle for teaching and learning citizen SMKN I Padang. Seeing the problems visitors less than 50%, then the use of the school library doing research with 227 respondents number of teachers and students SMKN 1 Padang. This study aimed to describe the use of the library by teachers and students of SMK 1 Padang. This type of research is descriptive. The population in this study were all students and teachers of SMK Padang in the year of 2014. In this research, there is only one variable, namely the use of libraries. Preparation of research instruments guided by the Likert Scale. Before being used as a data collection tool, first conducted trials to determine the validity and reliability of the instrument. Data were analyzed using the Product Moment Correlation formula and the KR 21. Based on the analysis of data, in general added that the use of the library by teachers and students in SMK 1 Padang in the unfavorable category. Keywords: Tinjauan Perpustakaan, Guru, Siswa